Detection of colour variations from gravitational microlensing observations in the quadruple quasar HE0435-1223: implications for the accretion disc - Sorgenfrei, Christian Matthias; Schmidt, Robert W.; Wambsganß, Joachim (Astronomy and astrophysics, 2025)
Aims. We present monitoring observations of quasar microlensing in the quadruple quasar HE0435-1223. The microlensing-induced light curves of the quasar images are chromatic, i.e. they depend on the applied filter band. Comparison with microlensing simulations allows us to infer properties of the accretion disc. Methods. We determined the R and V band light curves of the four images of HE0435-1223 from 79 and 80 epochs, respectively, taken from 2014 to 2024 at the Las Cumbres Observatory using difference imaging analysis. We considered difference light curves to remove the intrinsic quasar variability. This reveals a prominent, long-term chromatic microlensing event in image B. We used microlensing light curve simulations with both Gaussian and standard thin accretion disc brightness profiles to analyse this signal. Results. The particularly strong signal observed in image B of HE0435-1223 makes it possible to detect the size ratio of the accretion disc in the R to the V band of and for the Gaussian and the thin disc model, respectively. These values are in agreement with standard thin disc theory. For the absolute size, we find large disc half-light radii of around 0.7-1.0 Einstein radii with an uncertainty of about 0.6 dex (depending on the filter bands and the models). Finally, our calculations show that image B undergoes caustic crossings about once per year.